Strategi Pengembangan Raung Konveksi dalam Peningkatan Volume Penjualan Pendekatan Blue Ocean Strategy - Ramadhan Eka Syahputra Nurhidayat; Nurul Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate development strategies that can increase the sales volume of Raung Konveksi company. Utilizing the Blue Ocean Strategy approach, the focus is on product innovation and marketing strategies to create new markets and expand market share. The research method employed is descriptive qualitative analysis, including case studies and customer surveys. The research findings indicate that the effective implementation of the Blue Ocean strategy can create differentiation and enhance competitiveness in the Raung Konveksi industry. This can be achieved through various means, including the development of unique and different products from competitors, as well as marketing strategies that introduce these products to new market segments. Through the Blue Ocean strategy, Raung Konveksi can avoid direct competition with existing competitors and create new space, enabling them to attract new customers and increase their sales volume. Overall, this research demonstrates that the Blue Ocean strategy can be an effective approach for Raung Konveksi company to achieve growth and success in facing fierce competition in their industry.